Effects of aeration modes and rates on nitrogen conversion and bacterial community in composting of dehydrated sludge and corn straw - Wang, Yuyun; Xu, PengXiang; Wang, Yue; Su, Jing; Xu, Zhi; Jiang, Zhengbo; Wei, Yuquan; Hang, Sheng; Ding, Xiaoyan; Zhang, Hao; Zhang, Longli; Liu, Yongdi; et al. (Frontiers in Microbiology, 2024)
Aeration is an important factor to regulate composting efficiency and nitrogen loss. This study is aimed to compare the effects of different aeration modes (continuous and intermittent) and aeration rate on nitrogen conversion and bacterial community in composting from dehydrated sludge and corn straw. Results showed that the intermittent aeration mode at same aeration volume was superior to the continuous aeration mode in terms of NH3 emission reduction, nitrogen conversion and germination index (GI) improvement. Intermittent aeration mode with 1200 L/h (aeration 5 min, stop 15 min) [K5T15 (V1200)] and 300 L/h of continuous aeration helped to the conservation of nitrogen fractions and accelerate the composting process. However, it was most advantageous to use 150 L/h of continuous aeration to reduce NH3 emission and ensure the effective composting process. The aeration mode K5T15 (V1200) showed the fastest temperature rise, the longer duration of thermophilic stage and the highest GI (95%) in composting. The cumulative NH3 emission of intermittent aeration mode was higher than continuous aeration mode. The cumulative NH3 emission of V300 was 23.1% lower than that of K5T15 (V1200). The dominant phyla in dehydrated sludge and corn straw composting were Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes. The dominant phylum in the thermophilic stage was Firmicutes (49.39%~63.13%), and the dominant genus was Thermobifida (18.62%~30.16%). The relative abundance of Firmicutes was greater in the intermittent aeration mode (63.13%) than that in the continuous aeration mode (57.62%), and Pseudomonas was dominant in composting with lower aeration rate and the lowest NH3 emission. This study suggested that adjustment to the aeration mode and rate could affect core bacteria to reduce the nitrogen loss and accelerate composting process.